The lightning flash - Cooray, Vernon (Institution of Engineering and Technology, 2003)
The book reviews developments in the following fields: charge structure and geographical variation of thunderclouds; thunderstorm electrification mechanism; electrical discharge mechanism; lightning flash mechanism; electromagnetic field computation from lightning discharge; return stroke mathematical modelling; effects of propagation on electric radiation field; interaction of electromagnetic fields generated by lightning with overhead electrical networks; EMC; lightning protection; and electrical aspects of lightning strike to humans.